Interactive Media Development Training for Primary MGMP Mathematics Teachers to Support the Project for Strengthening Pancasila Student Profiles - Ramdani, Nurlailatun; Nurwalidainismawati, Nurwalidainismawati; Ardiansyah, Randi (Abdi Masyarakat, 2024)
The interactive media development training for Mathematics teachers in the MGMP group at SMP Negeri 1 Soromandi aimed to enhance teachers' competencies in utilizing PhET and Wordwall technologies in project-based learning, in alignment with the Projek Penguatan Profil Pelajar Pancasila. This study used a questionnaire method to evaluate the training, with 21 participants providing assessments regarding the usefulness of the material, the effectiveness of the trainers, the use of media, and the challenges faced. The results of the analysis showed that the training was highly beneficial, with an average score of 5.00, and the interactive media used was deemed effective, with an average score of 4.90. The trainers were rated highly competent in delivering material systematically (average 4.95) and communicatively (average 4.90). However, the training manual received criticism for being incomplete (average 1.00), and some participants suggested extending the discussion time. This training successfully achieved its goal of improving teacher competencies, although improvements are needed in the training manual and discussion time allocation. Future training program development should focus on these two aspects to increase the effectiveness and sustainability of the training.